Analisis Perbandingan Kinerja Keuangan Perbankan Sebelum dan Sesudah Penerapan Good Corporate Governance Pada PT. BANK BJB SYARIAH, TBK - Malik AL Aziz, Fyla; Rahmawati, Rafika (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2019)
The study analyzed the financial performance conditions of BJB Syariah Bank before and afterthe implementation of GCG through measurement variables of ROA, BOPO, and CAR. The methodused to obtain research data is quantitative data methods. The ratios used to measure the financialperformance of Bank BJB Syariah are ROA, BOPO, CAR. Data analysis in this study is using datanormality test and hypothesis testing using paired sample t-test. Nowadays it shows that the financialperformance condition of Bank BJB Syariah for ROA after the application of GCG is better than theROA before the implementation of GCG with an average ROA after 0.0500%> than the average ROAbefore GCG which is 0.0150%. BOPO after GCG implementation is better than BOPO before GCGimplementation with an average BOPO after GCG 111.2500%> than the average BOPO before GCG9.5000%. CAR before GCG implementation is better than CAR after GCG implementation with anaverage CAR before GCG 34.5000%> than the average CAR after GCG 18.5000%. Based on theresults of the data normality test that has been done, it is found that the data is normally distributed.Hypothesis test results using the Paired Sample t-test, namely for the ROA ratio there is no significantdifference to the financial performance of BJB Syariah Bank before and after the implementation ofGCG with a significance value of ROA 0.015> 0.05. There is no significant difference in the BOPOratio on the financial performance of Bank BJB Syariah before and after the implementation ofGCG with a significance value of BOPO 0.226> 0.05. The CAR ratio is a significant difference tothe financial performance of Bank BJB Syariah before and after the implementation of GCG with asignificant value of CAR, namely 0.001 <0.05.